1999
DOI: 10.4269/ajtmh.1999.60.831
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic activity of atovaquone against Plasmodium falciparum in humans.

Abstract: Abstract. The prophylactic antimalarial activity of atovaquone was determined in a randomized, double-blind, placebocontrolled study of healthy volunteers who were challenged by the bite of Plasmodium falciparum-infected Anopheles stephensi. Subjects were randomly assigned to one of three groups: six received seven daily doses of 750 mg of atovaquone, starting the day before challenge; six received a single dose of 250 mg of atovaquone the day before challenge; and four received placebo. Polymerase chain react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 31 publications
3
43
0
Order By: Relevance
“…Atovaquone was also effective as a single agent in prevention of falciparum malaria in a mosquito challenge study (115). In that randomized, double-blind, placebo-controlled study, subjects were infected with P. falciparum and given low-dose atovaquone (250 mg administered once 1 day prior to infection, six subjects), high-dose atovaquone (750 mg daily for 7 days beginning 1 day prior to infection, six subjects), or placebo (four subjects).…”
Section: Review Of Clinical Trialsmentioning
confidence: 99%
“…Atovaquone was also effective as a single agent in prevention of falciparum malaria in a mosquito challenge study (115). In that randomized, double-blind, placebo-controlled study, subjects were infected with P. falciparum and given low-dose atovaquone (250 mg administered once 1 day prior to infection, six subjects), high-dose atovaquone (750 mg daily for 7 days beginning 1 day prior to infection, six subjects), or placebo (four subjects).…”
Section: Review Of Clinical Trialsmentioning
confidence: 99%
“…This was further suggested in a small trial [6] of healthy volunteers who received atovaquone or placebo before being challenged by bites of P. falciparuminfected mosquitoes. Whereas all placebo recipients developed malaria, six subjects who received a single, 250-mg dose of atovaquone on the day before challenge were protected, even though the drug levels, by day 6.5, were profoundly sub-therapeutic, suggesting that parasites had been eliminated prior to the establishment of erythrocytic infection.…”
Section: Methodsmentioning
confidence: 96%
“…Prophylactic efficacy and safety have been assessed in three randomized, placebo-controlled trials in residents of endemic areas, as reported by Lell and colleagues, Shanks and coworkers, and Sukwa and colleagues [2][3][4]. An open-label trial with nonimmune subjects exposed to P. falciparum malaria was reported by van der Berg and colleagues [5], and a randomized, controlled trial of volunteers given atovaquone or placebo and challenged with P. falciparum-infected mosquitoes, was reported by Shapiro and colleagues [6].…”
Section: Methodsmentioning
confidence: 99%
“…Atovaquone/proguanil is a once daily medication that is effective against both the erythrocytic and exoerythorcytic stages of malaria making this an acceptable choice not only for P. falciprum, but also P. vivax and P. ovale, both of which have hepatic life cycles. The efficacy of atovaquone as a causal prophylaxis was seen in a small volunteer challenge study in which it was shown that parasites were eliminated prior to the establishment of erythrocytic infection, thus supporting causal efficacy (Shapiro et al, 1999). Atovaquone/proquanal has demonstrated efficacy for malaria prophylaxis in areas with predominantly P. vivax (Soto et al, 2006).…”
Section: Atovaquone and Proguanil Hydrochloridementioning
confidence: 94%